EXPLORING THE CONSTRUCTION OF NOVICE EFL TEACHERS’ IDENTITY IN UNIVERSITY CONTEXT - Arif Angga Putra (Graduate Program, University of Islam Malang, 2021)
The issue about teacher identity has been interesting to be observed by researchers in the past decade. Understanding teacher identity becomes important for teacher; both novice and experienced teacher where they need to shape and to develop professional identity as the teacher. This narrative study has sought to explore the construction of novice EFL teachers’ identity reflected in university context. The data were derived from two novice university EFL teachers through narrative frames and semi-structured interviews. The data were analyzed using TESOL teacher identity frameworks by Pennington (2014). The result shows that novice university EFL teachers constructed their identity through the implementations of teaching practices within professional development in university context that includes teaching strategies application, the knowledge field mastering, professional comprehension, teaching commitment, and life need fulfillment. The participants’ identity was also affected by intrinsic and extrinsic factors. Intrinsic factors include participants’ teaching motivation, satisfaction, and competence. Extrinsic factors include participants’ work environment, job career, students’ need and interaction with colleagues. Thus, understanding the construction of EFL novice teachers will contribute the platform for EFL teachers mainly for native teachers to prepare their professional teaching practice particularly in the university context.Keywords: Teacher Identity, Novice EFL Teacher, TESOL teacher Identity Framework, University Context